2020
DOI: 10.1002/jaba.711
|View full text |Cite
|
Sign up to set email alerts
|

Treating food selectivity as resistance to change in children with autism spectrum disorder

Abstract: Change-resistant behavior, such as rigid and selective food consumption, is a core symptom of autism that can have significant negative consequences for the child (Flygare Wallén et al., 2018; Levy et al., 2019). In the current study, we used a matching-law-based intervention (Fisher et al., 2019) to treat the change-resistant feeding behavior of 7 young children with autism. The feeder gave the participant a choice between a change-resistant and an alternative food during free-and asymmetrical-choice conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 50 publications
0
6
0
7
Order By: Relevance
“…For example, Project imPACT uses specific procedures to train parents to promote their children's social‐communication skills. Although these specific procedures are clearly effective for some individuals, they are less likely to be effective for children with ASD whose most troubling issues are rituals, compulsions, resistance to change, and associated destructive behavior when someone interrupts their daily routine (e.g., Crowley et al, 2020; Fisher et al, 2019) Thus, providing parents with a broader variety of ABA skills is important because parents often must address skill deficits and problem behavior simultaneously, and they may have to change ABA procedures when the first one implemented is not effective.…”
mentioning
confidence: 99%
“…For example, Project imPACT uses specific procedures to train parents to promote their children's social‐communication skills. Although these specific procedures are clearly effective for some individuals, they are less likely to be effective for children with ASD whose most troubling issues are rituals, compulsions, resistance to change, and associated destructive behavior when someone interrupts their daily routine (e.g., Crowley et al, 2020; Fisher et al, 2019) Thus, providing parents with a broader variety of ABA skills is important because parents often must address skill deficits and problem behavior simultaneously, and they may have to change ABA procedures when the first one implemented is not effective.…”
mentioning
confidence: 99%
“…For instance, we adopted the description of asymmetrical-choice options for the procedures using differential reinforcement in concurrent-operant arrangements because it is a term that appears early in the literature base (e.g., McDowell, 1989;Fisher & Mazur, 1997) and is an accurate description of the conditions, which consist of purposefully programming differences in the reinforcement parameters across response options. Although several of the reviewed experiments also used this label directly (e.g., Crowley et al, 2020;, we observed multiple labels for procedures with common features including choicemaking (e.g., Peck Peterson et al, 2009), DRA without extinction (e.g., Athens & Vollmer, 2010;Briggs et al, 2019), and FCT with concurrent operants (e.g., Davis et al, 2018). Having some continuity in the verbal behavior around choice-based interventions may help systematize the literature moving forward and may even facilitate advancements in choice-based technologies through better communication in the research community.…”
Section: Discussionmentioning
confidence: 99%
“…We retained Cannella's category label for building choice opportunities into daily contexts. In place of the category used by Cannella et al, "effects of choice-making," we created a category for differential reinforcement with concurrent asymmetrical-choice options, which has been used in previous literature (Crowley et al, 2020;Fisher & Mazur, 1997;McDowell, 1989). The purpose of this change was to use a more descriptive label that more clearly differentiates between the two intervention categories and create a label that encompassed an arrangement that appeared with frequency in our review of abstracts.…”
Section: Design Independent and Dependent Variables And Intervention ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the percentage of independent acceptance and mouth cleansing increased for the applied behavioral analytical intervention group, but not for the waitlist control group until they implemented the intervention. In a recent study, the authors gave seven participants a choice between a change-resistant food and an alternative food during free- and asymmetrical-choice conditions [ 97 ]. Alternative-food consumption increased for two participants during asymmetrical choice when the feeder provided a preferred item for consuming the alternative food and no programmed consequence for consuming the change-resistant food.…”
Section: Clinical Interventionsmentioning
confidence: 99%